The image of an actor in the modern theater - Билалов, Ерлан (Pedagogy and Psychology, 2020)
The purpose of the study is to determine the main features of the appearance of the actor and show that he is an indispensable carrier of today’s stage art. In the article, focusing on the skill of the actor, universal human values and the specifics of theatrical art are also considered. The content of the concept of the phrase «Theater for people» is determined and demonstrated in the actor’s special mission: to convey the feelings, excitement of a living person and give true feelings of the whole atmosphere of what is happening. The idea is substantiated that nothing can overshadow the game of a professional actor, as a material of live communication between him and the audience, allowing you to feel all the nuances of the action. Scientific novelty lies in the study of the degeneration and development of acting skills against the backdrop of a developing age of technology and the introduction of innovative special effects. As a result, the fact that innovative technologies should help the viewer understand the essence of the production is highlighted and characterized, and the actor’s skill should be directed towards the universal values of the viewer.